Family farming’s competitive performance in Santa Catarina - Sousa, Eliane Pinheiro de; Bender Filho, Reisoli; Coronel, Daniel Arruda; Amorim, Airton Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The aim of this work is to identify the determinant factors of family farming competitiveness in municipalities of Santa Catarina (SC) through the Index of Competitive Performance of Family Farming (IDAF) and multiple regression analysis and also to check for significant differences in competitiveness of family farming between mesoregions that State through parametric tests of Levene and of t Student for unpaired data. A sample of 183 municipalities of Santa Catarina has been considered out of the total of 293 municipalities in this state. The data has been collected from Agricultural Census (2006), which is publicized in the website of Brazilian Institute of Geography and Statistics (IBGE). The results indicate that family farming in municipalities of Santa Catarina is, in general, low and intermediate level of competitiveness. The regression analysis confirmed positive relationship between the annual income and the factors of competitiveness analyzed. In addition, it was found that there are significant differences in the average competitiveness of the family farming between mesoregion of Vale do Itajaí and mesoregions of Florianópolis and Serrana. Therefore, it is concluded that there is great heterogeneity in municipalities of Santa Catarina in relation to the competitive performance of family farming.